Nanosized Magnesium Electrochemically Deposited on a Carbon Nanotubes Suspension: Synthesis and Hydrogen Storage - Shen, Chaoqi; Aguey-Zinsou, Kondo-Francois (Frontiers in Energy Research, 2017)
Herein, we report on a novel method for deposition of magnesium (Mg) nanoparticles at the surface of carbon materials. Through the suspension of carbon nanotubes (CNTs) in an electrolyte containing di-n-butylmagnesium as a precursor, Mg nanoparticles were effectively deposited at the surface of the CNTs as soon as these touched the working electrode. Through this process, CNTs supported Mg particles as small as 1 nm were synthesized and the distribution of the nanoparticles was found to be influenced by the concentration of the CNTs in the electrolyte. Hydrogenation of these nanoparticles at 100°C was found to lead to low temperature hydrogen release starting at 150°C, owing to shorter diffusion paths and higher hydrogen mobility in small Mg particles. However, these hydrogen properties drastically degraded as soon as the hydrogenation temperature exceeded 200°C and this may be related to the low melting temperature of ultrasmall Mg particles.